Examining the Relationship among Online Brand Elements, Dialogic Communication and Online Brand Personality - Amartey, Rhodalene (European Journal of Business and Management, 2019)
The objective of this study is to assess the relationship among online brand elements, dialogic communication and brand personality. The study used survey research design. The unit of analysis was the universities in Ghana. Descriptive statistics, confirmatory factor analysis and logistic regression were used to analyze the data. The findings show that brand and website elements significantly influence three brand personality dimensions namely: competence, excitement, and sophistication. The findings also revealed that websites with high dialogic communication features would significantly enhance the relationship between brand and website elements and the university brand personality dimensions as compared to those with low dialogic communication features.
Research Article
Keywords: Brand Personality; Brand Elements; Dialogic Communication; Logistic Regression; Universities in Ghana